Suffering amid a pandemic: The televised rejection of non-social amelioration program beneficiaries - De Leon, Anna Katherine Dela Cuesta (Animo Repository, 2022)
Mediation of news offers a performative function which can bring people’s attention towards human suffering, but it can also evoke representations that shape public behavior and ethical norms. By using Lilie Chouliaraki’s analytics of mediation as a springboard, this research proposes two distinct regimes of pity or emerging characteristics of reports that were evident in two primetime news programs in the Philippines showcasing proximal suffering during a pandemic. The first regime is Patronage News, which is a concept patterned from the ancient Roman society’s patronus-cliens relationship called clientela or its legal term patrocinium in which patrons give support to their plebeian clients who, in turn, provide services and loyalty to them. This type of news narrativizes suffering to entrench the media’s role as a benefactor providing public service that fosters clientelistic ties between broadcast institutions and viewers. Meanwhile, the other type is Reflective News, which is derived from the Latin word reflectere which connotes ‘to bend something back.’ Similar to a mirror when the light waves bounce back to show a person’s reflection, Reflective News facilitates emotional engagement by dramatizing the condition of the sufferers on television so that the audience can relate with them or have an inward contemplation without the urgency to act on the suffering. Through these regimes, the Philippine media evokes representations that reproduce existing power divides between the viewers and the sufferers. I provide empirical context to this argument through the mediation of suffering shown by TV Patrol and 24 Oras about citizens who were not included in the Philippine government’s Social Amelioration Program (SAP) during the Coronavirus disease 2019 (COVID-19) pandemic.